Preparation of pincer hafnium complexes for olefin polymerization - Kwon, Su Jin; Baek, Jun Won; Lee, Hyun Ju; Kim, Tae Jin; Ryu, Ji Yeon; Lee, Junseong; Shin, Eun Ji; Lee, Ki Soo; Lee, Bun Yeoul (Molecules, 2019)
Pincer-type [Cnaphthyl, Npyridine, Namido]HfMe2 complex is a flagship among the post-metallocene catalysts. In this work, various pincer-type Hf-complexes were prepared for olefin polymerization. Pincer-type [Namido,Npyridine,Namido]HfMe2 complexes were prepared by reacting in situ generated HfMe4 with the corresponding ligand precursors, and the structure of a complex bearing 2,6-Et2C6H3Namido moieties was confirmed by X-ray crystallography. When the ligand precursors of [(CH3)R2Si-C5H3N-C(H)PhN(H)Ar (R = Me or Ph, Ar = 2,6-diisopropylphenyl) were treated with in situ generated HfMe4, pincer-type [Csilylmethyl, Npyridine, Namido]HfMe2 complexes were afforded by formation of Hf-CH2Si bond. Pincer-type [Cnaphthyl, Sthiophene, Namido]HfMe2 complex, where the pyridine moiety in the flagship catalyst was replaced with a thiophene unit, was not generated when the corresponding ligand precursor was treated with HfMe4. Instead, the [Sthiophene, Namido]HfMe3-type complex was obtained with no formation of the Hf-Cnaphthyl bond. A series of pincer-type [Cnaphthyl, Npyridine, Nalkylamido]HfMe2 complexes was prepared where the arylamido moiety in the flagship catalyst was replaced with alkylamido moieties (alkyl = iPr, cyclohexyl, tBu, adamantyl). Structures of the complexes bearing isopropylamido and adamantylamido moieties were confirmed by X-ray crystallography. Most of the complexes cleanly generated the desired ion-pair complexes when treated with an equivalent amount of [(C18H37)2N(H)Me]+[B(C6F5)4]-, which showed negligible activity in olefin polymerization. Some complexes bearing bulky substituents showed moderate activities, even though the desired ion-pair complexes were not cleanly afforded.
Keywords: Alkenes; Catalysis; Crystallography, X-Ray; Hafnium; Magnetic Resonance Spectroscopy; Models, Molecular; Molecular Structure; Polymerization; Polymers; Hafnium complex; Olefin polymerization; Pincer complex; Post-metallocene